Supporting decision-making through technology - Charalambous, Andreas (My University, 2021)
Decision-making is a process through which an alternative is selected among others relied on gathered information. In order to select this alternative, it should have a reasonable priority based on its weight. Within the context of everyday practice in healthcare, clinical decision-making holds a fundamental place. Decision-making occurs numerous times throughout the management of patients (across the disease trajectory) and consists of a complex task which often involves diverse disciplines (i.e., decision-making within multidisciplinary team meetings). The complexity of the task can be further reinforced in patients with multimorbidity. In any clinical context, the task of decision-making carries with it the burden of responsibility for a patient's health and well-being. Echoing these challenging circumstances in healthcare, computerized clinical decision support systems (CDSSs) and medical diagnostic decision support systems (MDSS) have been developed to augment clinicians in their complex decision-making processes. These decision support systems represent a paradigm shift in healthcare today and their contribution to effective clinical decision-making is invaluable, however not without challenges. The scope of this chapter includes a review on the utilization of technological decision support systems within healthcare (and within specific diseases), an analysis of the limitations presented by these technologies, and finally present the features that the design of efficient, effective, and safe CDSS should incorporate.
Keywords: Decision-making; Clinical decision support systems; Healthcare